(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Smyk O. K. Health Promoting of younger pupils by the means of playing. The article deals with the essence of the concepts of «healthy lifestyle», «game activities»; presents results of influence of the game on a healthy lifestyle of the primary school pupils.